Pulsed radiofrequency alleviates neuropathic pain by upregulating MG53 to inhibit microglial activation - Yuanxin Huang; Yuanyue Huang; Xianglong Lv; Zilong Yu; Yue Qin; Xingyue Yang; Songsong An; Chunxin Wo; Lin Wang (European Journal of Medical Research)
Abstract Background Patients with neuropathic pain (NP) have significantly lower quality of life. Because the pathophysiology of NP is not fully understood, there is a lack of effective treatment for it in clinic. This study set out to investigate the precise mechanism by which pulsed radiofrequency (PRF) alleviated NP. Method The rat models of chronic constriction injury of the sciatic nerve (CCI) were established to simulate the occurrence of NP, following with measuring MWT and TWL to evaluate the pain of the rats. HE staining was utilized to observe the rat spinal cord tissue pathology. The expression of MG53, ATF4 and CHOP was evaluated by qRT-PCR and WB, while the expression of inflammatory factors was measured by ELISA. In addition, immunofluorescence assay was used to detect the expression of MG53 and Iba-1. Result PRF treatment alleviated NP in CCI rats, as well as upregulating the expression of MG53 and inhibiting microglial activation. After MG53 knockdown, the remission of NP by PRF was significantly weakened, but microglial activation and endoplasmic reticulum stress (ERS) exhibited enhancement. Therefore, PRF inhibited microglial activation by upregulating MG53. After injection of ERS inducer in CCI rats, the inhibition effect of overexpressed MG53 on microglial activation and its alleviation effect on NP were reversed. Consequently, MG53 played a role in suppressing microglial activation by mediating the inhibition of ERS. Conclusion PRF attenuated microglial activation by upregulating MG53 to inhibit ERS, resulting in the alleviation of NP in CCI rats.